Virulence of entomopathogenic fungi against fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) under laboratory conditions - Idrees, Atif; Afzal, Ayesha; Qadir, Ziyad Abdul; Li, Jun (Frontiers in Physiology, 2023)
Maize is an essential crop of China. The recent invasion of Spodoptera frugiperda, also known as fall armyworm (FAW), poses a danger to the country's ability to maintain a sustainable level of productivity from this core crop. Entomopathogenic fungi (EPF) Metarhizium anisopliae MA, Penicillium citrinum CTD-28 and CTD-2, Cladosporium sp. BM-8, Aspergillus sp. SE-25 and SE-5, Metarhizium sp. CA-7, and Syncephalastrum racemosum SR-23 were tested to determine their effectiveness in causing mortality in second instars, eggs, and neonate larvae. M. anisopliae MA, P. citrinum CTD-28, and Cladosporium sp. BM-8 caused the highest levels of egg mortality, with 86.0, 75.3, and 70.0%, respectively, followed by Penicillium sp. CTD-2 (60.0%). Additionally, M. anisopliae MA caused the highest neonatal mortality of 57.1%, followed by P. citrinum CTD-28 (40.7%). In addition, M. anisopliae MA, P. citrinum CTD-28, and Penicillium sp. CTD-2 decreased the feeding efficacy of second instar larvae of FAW by 77.8, 75.0, and 68.1%, respectively, followed by Cladosporium sp. BM-8 (59.7%). It is possible that EPF will play an important role as microbial agents against FAW after further research is conducted on the effectiveness of these EPF in the field.